EVALUASI EFISIENSI SIRKULASI TERMINAL ANGKUTAN PERKOTAAN DI TERMINAL BUS MANGKANG - Agusvan Syarif; Suis Ogeswartomal; Bambang Riyanto; Supriyono Supriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Terminal Mangkang which was a type-C terminal, is now upgraded to be a type-A terminal, located in the western side of Semarang City. Terminal Mangkang, specifically the urban transit area, has several issues, for instance the lack of vehicle circulation system due to several meeting points of the arriving and departing vehicles. Besides, passengers get on and off the vehicles at improper places. Therefore, is a necessity to evaluate the efficiency of vehicle circulation system at the urban transit area terminal. Data was collected by giving questionnaires to 100 respondents with a sampling method, and recording method of vehicle circulation time. The questionnaire consists of ten questions focusing on travel origin and destination, type of public transit choice, and movement pattern of passengers on and off vehicle inside and outside the terminal. The result showed that majority of passengers (54%) came from western side of the city and 40% passengers used NBAK (Non Bus Angkutan Kota/ Non-Bus City Transport). For passenger movement pattern, the majority of passengers (47%) get off the vehicle inside the terminal, located at the entrance after the inclining road of TPR 41% passengers would wait for the vehicle at the exit way outside the terminal. According to the performance comparison of each type of terminal, recomendation type 2 model has seventy-eight-second of efficiency on circulation time compared to the existing terminal circulation. This type 2 model will decrease the tendency of passengers to switch vehicles outside the terminal. This study recommends a rearrangement of terminal layout to facilitate the activity of circulating passengers for each type of vehicle operating in the public transport terminal. The type 2 model may be considered by the stakeholders in the rearrangement of the terminal layout.